Implementation of Moderate Islamic Values as a Foundation for Inclusive Religious Character - Ikhwan Kharisma (Al-Qalam Institute, 2024)
This study examines the integration of moderate Islamic values in the basic education curriculum in Indonesia, focusing on SDN 1 Gending in Probolinggo. The primary purpose of this research is to explore how moderate Islamic values are applied in the learning process, both through Islamic Religious Education (PAI) lessons and other subjects such as PPKn and Social Studies. Given the importance of education that prioritizes tolerance and inclusivity in a pluralistic society, this study seeks to understand the application of these values in the daily life of schools and their impact on students' character. A qualitative approach collects data through teacher interviews, direct observation, and document analysis. The study results show that SDN 1 Gending has successfully integrated moderate Islamic values into the curriculum, focusing on respect for differences, equality, and peaceful coexistence. Nonetheless, challenges remain in implementing a moderate curriculum, especially in addressing differences in understanding between teachers and limited resources. These findings provide important insights for the development of moderation-based character education in primary schools and strengthen education's role in creating a more tolerant and inclusive society.